The Influence of an Observer’s Value Orientation and Personality Type on Attitudes Toward Whistleblowing - Park, Heungsik (Journal of business ethics, 2014)
This study examines the influence of an observer’s value orientation and personality type on attitudes toward whistleblowing. Based on a review of the literature we generated three hypotheses to explain the relationship between these two factors and attitudes toward whistleblowing, and these were tested using data collected from 490 university students in South Korea. The survey comprises two parts, a measure of MBTI personality types, and a section assessing value orientations and attitudes toward whistleblowing. Regression analysis was conducted to clarify the influence of the independent variables. The study offers two main contributions. First, it examines what role an observer’s value orientation and personality type play in determining the attitudes. Second, it provides insights into designing customized ethical training programs and developing policy aimed at changing negative attitudes toward whistleblowing.